2012
DOI: 10.1371/journal.pcbi.1002702
|View full text |Cite
|
Sign up to set email alerts
|

The p7 Protein of Hepatitis C Virus Forms Structurally Plastic, Minimalist Ion Channels

Abstract: Hepatitis C virus (HCV) p7 is a membrane-associated oligomeric protein harboring ion channel activity. It is essential for effective assembly and release of infectious HCV particles and an attractive target for antiviral intervention. Yet, the self-assembly and molecular mechanism of p7 ion channelling are currently only partially understood. Using molecular dynamics simulations (aggregate time 1.2 µs), we show that p7 can form stable oligomers of four to seven subunits, with a bias towards six or seven subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 75 publications
3
79
0
2
Order By: Relevance
“…The stoichiometry of p7 channel complexes has been reported as both hexameric and heptameric in membrane-mimetic detergents and lipid bilayers, with some studies reporting mixtures of both forms (Clarke et al, 2006;Griffin et al, 2003;Luik et al, 2009;OuYang et al, 2013;StGelais et al, 2009;Whitfield et al, 2011). Molecular dynamics confirms that both species are theoretically viable, although both display a degree of metastability (Chandler et al, 2012). The membrane environment appears to exert significant influence over p7 structure and channel activity, with potential fluctuations in both the monomeric and oligomeric form proposed to regulate its behaviour (Whitfield et al, 2011 Elegant transmission electron microscopy reconstruction studies of hexameric genotype 2a p7 channel complexes in detergent micelles revealed a flower-shaped channel complex with both N/C termini membrane-exposed and oriented to the broad 'petals' of the channels by immuno-gold labelling, consistent with a hairpin monomeric conformation (Luik et al, 2009).…”
Section: Hcv P7mentioning
confidence: 85%
See 1 more Smart Citation
“…The stoichiometry of p7 channel complexes has been reported as both hexameric and heptameric in membrane-mimetic detergents and lipid bilayers, with some studies reporting mixtures of both forms (Clarke et al, 2006;Griffin et al, 2003;Luik et al, 2009;OuYang et al, 2013;StGelais et al, 2009;Whitfield et al, 2011). Molecular dynamics confirms that both species are theoretically viable, although both display a degree of metastability (Chandler et al, 2012). The membrane environment appears to exert significant influence over p7 structure and channel activity, with potential fluctuations in both the monomeric and oligomeric form proposed to regulate its behaviour (Whitfield et al, 2011 Elegant transmission electron microscopy reconstruction studies of hexameric genotype 2a p7 channel complexes in detergent micelles revealed a flower-shaped channel complex with both N/C termini membrane-exposed and oriented to the broad 'petals' of the channels by immuno-gold labelling, consistent with a hairpin monomeric conformation (Luik et al, 2009).…”
Section: Hcv P7mentioning
confidence: 85%
“…Further along the spectrum towards a pore, HCV p7 has been shown to adopt both single-channel and 'burst-activity' behaviour in bilayers, with single-channel activity also comprising more than one conductance state (Chew et al, 2009;Clarke et al, 2006;Griffin et al, 2003;Pavlović et al, 2003;Premkumar et al, 2004;Whitfield et al, 2011). This may reflect p7 behaviour whilst conducting a non-preferred ionic substrate, although p7 activity is also differentially modulated by several factors, including virus genotype (Atkins et al, 2014), the formation of different oligomers (Clarke et al, 2006;Luik et al, 2009) and membrane composition (Whitfield et al, 2011), all of which may influence the meta-stable nature of channel complexes (Chandler et al, 2012).…”
Section: General Viroporin Characteristicsmentioning
confidence: 99%
“…Notably, the precise oligomeric state of p7 is still debated, with both hexameric (2,13,15) and heptameric (12,15) species having been reported. Each p7 monomer consists of two transmembrane segments separated by a hydrophilic loop orientated toward the cytosol.…”
mentioning
confidence: 99%
“…Regarding the ion-channeling activity of p7, the ion specificity has not been fully established (15), although a preference for the channeling of cations has been reported (5). Recently, p7-mediated transfer of protons across intracellular membranes was observed (17).…”
mentioning
confidence: 99%
“…Posee un genoma RNA lineal de aproximadamente 10.000 nucleótidos (Chandler et al, 2012). Generalmente es transmitida por el uso de drogas y transfusiones de sangre, aunque también se puede dar por contacto sexual y transmisión vertical.…”
Section: Virus Epstein-barr (Ebv) El Virus De Epstein-barr (Ebv)unclassified